2005
DOI: 10.1128/aem.71.6.3119-3125.2005
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Diversity of Viruses in Six Delaware Soils

Abstract: The importance of viruses in marine microbial ecology has been established over the past decade. Specifically, viruses influence bacterial abundance and community composition through lysis and alter bacterial genetic diversity through transduction and lysogenic conversion. By contrast, the abundance and distribution of viruses in soils are almost completely unknown. This study describes the abundance and diversity of autochthonous viruses in six Delaware soils: two agricultural soils, two coastal plain forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
214
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(239 citation statements)
references
References 61 publications
21
214
3
1
Order By: Relevance
“…Results indicated that, phage active against Bt may be present in soil or integrated with host genome (lysogeny) or as independent linear replica within the cell. These results are in accordance with finding of [19,26,27,41,43,48]. Electron microscopic studies of the isolated phages (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Results indicated that, phage active against Bt may be present in soil or integrated with host genome (lysogeny) or as independent linear replica within the cell. These results are in accordance with finding of [19,26,27,41,43,48]. Electron microscopic studies of the isolated phages (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…It was speculated that this may happen because viruses persist longer at cooler temperatures (Yates et al 1990). Williamson et al (2005) verified that viruses persist infectious for longer times under wetland soils. This may be due to the presence of thicker water films and smaller interfacial areas, since such interfaces may inactivate viral particles (Zhuang & Jin 2003).…”
Section: Enteric Viruses In Soil and Sedimentsmentioning
confidence: 93%
“…It is a general consensus that the transport of pathogens in the subsurface depends on the extent of their retention of soil particles and their environmental resistance (Keeley et al 2003). The maintenance of these agents may also be affected by the isoelectric point and hydrophobicity of capsid proteins (Williamson et al 2005). It was demonstrated that clay minerals in soil may protect viral particles (Nasser et al 2002).…”
Section: Enteric Viruses In Soil and Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, agricultural soils usually harbor a phage count of approximately 10 /mL [25][26][27][28].…”
Section: Lytic Bacteriophage Structurementioning
confidence: 99%